Eating habits and lifestyles of medical students at the beginning of the Covid-19 pandemic eating: Hábitos alimentarios y estilo de vida de los estudiantes de medicina a inicios de la pandemia Covid-19 - Espinoza-Gutierrez, Geraldine A. (2022)
The mortality rate from COVID-19 in Peru continues to increase, considered by January 24, 2022, as the third country with the most cases and deaths in all of South America. Connement favors an extremely sedentary lifestyle, physical inactivity, and poor eating practices causing serious health risks.   Objectives: Describe the eating habits and lifestyles of medical students during the CoVID-19 quarantine.   Materials and Methods: Multicenter Descriptive Cross-sectional Study.   Results: A total of 886 medical students participated. The female gender prevailed with 81.49% (n = 722) compared to the male gender with 18.51% (n = 164). Regarding the perception of health, only 4.51% (n= 40) rated it as low and the remaining 95.49% rated it as satisfactory (n= 111), good (n= 495), very good (n= =200) and excellent (n=40). The predominant healthy habits were not smoking 91.08% (n= 807) and doing physical activity 78.78% (n= 698); During the pandemic, physical activity was reduced, reaching 53.95% of students.   Conclusions: Medical students during the COVID-19 connement stage, medical students opted for regular healthy eating habits and preventive behaviors. However, daily physical activity was predominantly low.